Household Water Security and the Human Right to Water and Sanitation - Chenoweth, Jonathan; Malcolm, Rosalind; Pedley, Steve; Kaime, Thoko (Taylor and Francis, 2013)
This chapter focuses on water security at the household level. Grey and Sadoff (2007, p548) give a general definition of water security as ‘the availability of an acceptable quantity and quality of water for health, livelihoods, ecosystems and production, coupled with an acceptable level of water-related risks to people, environments and economies’. Applying the concept of water security at the household scale would suggest that water security means ensuring households have a sufficient quantity of water of sufficient quality to maintain the health of household members. Household water security is closely tied to sanitation provision, since achieving household access to acceptable quality water for health and livelihoods generally requires sanitation provision also; a lack of sanitation in a community makes the provision of safe water supply in that same community difficult to achieve.
CRIS-Team Scopus Importer:2023-03-21